2015
DOI: 10.1021/acs.inorgchem.5b01477
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Photochemical, and Redox Properties of Gold(I) and Gold(III) Pincer Complexes Incorporating a 2,2′:6′,2″-Terpyridine Ligand Framework

Abstract: Reaction of [Au(C6F5)(tht)] (tht = tetrahydrothiophene) with 2,2′:6′,2″-terpyridine (terpy) leads to complex [Au(C6F5)(η1-terpy)] (1). The chemical oxidation of complex (1) with 2 equiv of [N(C6H4Br-4)3](PF6) or using electrosynthetic techniques affords the Au(III) complex [Au(C6F5)(η3-terpy)](PF6)2 (2). The X-ray diffraction study of complex 2 reveals that the terpyridine acts as tridentate chelate ligand, which leads to a slightly distorted square-planar geometry. Complex 1 displays fluorescence in the solid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 54 publications
3
21
0
Order By: Relevance
“…The redox stability of gold­(I) complexes has limited development of complementary methods utilizing redox gold catalysts. This work describes a gold catalyzed decarboxylative cross-coupling reaction, where the redox events are proposed to occur from a gold­(I) complex. Pioneering studies demonstrated that gold­(I) complexes can participate in oxidative addition with methyl iodide, , trifluoromethyl iodide, , aryl diazonium salts, iodine­(III) reagents, and other strong oxidants. ,, Initially Lloyd-Jones and co-workers demonstrated a catalytic oxidative coupling of aryl-silanes in the presence of a strong acid and a stoichiometric iodine­(III) oxidant (Scheme a). , A limiting feature of this and subsequent work ,, is that the site selectivity of C–H bond activation is governed by an apparent electrophilic aromatic substitution (EAS) mechanism. Patil and co-workers demonstrated a dual gold/photoredox catalyzed cross-coupling with aryl silanes or aryl stannanes, which is thought to occur via a radical mechanism (Scheme b) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The redox stability of gold­(I) complexes has limited development of complementary methods utilizing redox gold catalysts. This work describes a gold catalyzed decarboxylative cross-coupling reaction, where the redox events are proposed to occur from a gold­(I) complex. Pioneering studies demonstrated that gold­(I) complexes can participate in oxidative addition with methyl iodide, , trifluoromethyl iodide, , aryl diazonium salts, iodine­(III) reagents, and other strong oxidants. ,, Initially Lloyd-Jones and co-workers demonstrated a catalytic oxidative coupling of aryl-silanes in the presence of a strong acid and a stoichiometric iodine­(III) oxidant (Scheme a). , A limiting feature of this and subsequent work ,, is that the site selectivity of C–H bond activation is governed by an apparent electrophilic aromatic substitution (EAS) mechanism. Patil and co-workers demonstrated a dual gold/photoredox catalyzed cross-coupling with aryl silanes or aryl stannanes, which is thought to occur via a radical mechanism (Scheme b) …”
Section: Introductionmentioning
confidence: 99%
“…Pioneering studies demonstrated that gold(I) complexes can participate in oxidative addition with methyl iodide, 19,20 trifluoromethyl iodide, 21,22 aryl diazonium salts, 23−29 iodine(III) reagents, 30−41 and other strong oxidants. 16,42,43 Initially Lloyd-Jones and co-workers demonstrated a catalytic oxidative coupling of aryl-silanes in the presence of a strong acid and a stoichiometric iodine(III) oxidant (Scheme 1a). 31,34 A limiting feature of this and subsequent work [35][36][37][38][39][40]44,45 is that the site selectivity of C−H bond activation is governed by an apparent electrophilic aromatic substitution (EAS) mechanism.…”
mentioning
confidence: 99%
“…Complexes with dual emission are particularly interesting from the viewpoint of practical applications, since this type of photophysical behaviour makes, in principle, 100 % harvesting of excitation energy possible (e.g., in OLEDs) and also opens up an avenue to the fabrication of white‐light devices, so‐called white‐light organic light‐emitting devices (WOLEDs) , . In this respect, it must be mentioned that various phosphine and alkynyl ligands with fluorescent aromatic backbones were widely used as auxiliary chromophoric centres in gold(I) complexes,, , , whereas analogous chemistry with N‐donor aromatic ligands is relatively less successful,, and the obtained complexes are either nonluminescent under ambient conditions, , or display a very weak triplet emission with nearly negligible contribution from the N‐donor‐ligand chromophores. It is also worth noting that the known pyridyl–gold–alkynyl complexes (L–Au–C 2 Ph) proved to be only stable provided that the pyridyl ligands possessed strong electron‐donating substituents, like NH 2 and NMe 2 (4‐NH 2 Py and 4‐dmap).…”
Section: Introductionmentioning
confidence: 99%
“…As shown in the anodic profile, the cathodic scan shows irreversible waves in all cases, but when the electrode potential is increased to more negative potentials, an exponential current appears. 45 In all cases, the first anodic and cathodic peak are very sensitive to the scan rate since both move to more anodic or more cathodic potentials, respectively, when the scan rate increases. The electrochemical data (anodic and cathodic peaks potentials (E ap , E cp ), and anodic and cathodic peaks currents (i ap , i cp )) are summarized in table 4.…”
Section: Electrochemical Behaviourmentioning
confidence: 94%